Colorless high-transmittance flame-retardant phosphorylated nanocellulose reinforced PVA film prepared based on secondary swelling

The cellulose is initially swollen and phosphorylated by NaOH solution, which solves the problems of phosphorus content and easy degradation and discoloration of phosphorylated cellulose, and a colorless and transparent phosphorylated nanocellulose reinforced PVA film was prepared, achieving better flame retardant and mechanical properties.

CN119708562AActive Publication Date: 2025-03-28SICHUAN UNIV

Patent Information

Application Number
CN202411827884.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In the prior art, the phosphorus content and easy degradation and discoloration of phosphoric cellulose have a "seesaw" problem, and it is difficult to prepare a colorless and transparent phosphorylated nanocellulose-reinforced PVA film.

Method used

The cellulose was initially swelled by NaOH solution, urea and NH4H2PO4 were added and mixed, and after drying, solid phase reaction was carried out to increase the degree of phosphorylation, phosphorylated nanocellulose with high phosphorus content, and a colorless and transparent enhanced PVA film was prepared by homogenization treatment.

Benefits of technology

While improving the mechanical properties, the colorless transparency of the film is maintained, and a better flame retardant effect is obtained by lower flame retardant addition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708562A_ABST
    Figure CN119708562A_ABST
Patent Text Reader

Abstract

The invention provides a colorless high-permeability flame-retardant phosphorylated nanocellulose reinforced PVA film prepared based on secondary swelling, which is characterized in that cellulose is preliminarily swelled by a NaOH solution, then quantitative urea and NH4H2PO4 are added to be effectively mixed with the cellulose, solid-phase reaction is performed after water is dried, the subsequent phosphorylation degree is increased while secondary swelling is performed, and the film is prepared by using a one-step method to prepare the colorless high-permeability flame-retardant phosphorylated nanocellulose reinforced PVA film. The phosphorylated nanocellulose with high phosphorus content is prepared and serves as a filler, and the flame-retardant, colorless and transparent reinforced PVA film can be prepared through a solution method for molding. Through secondary swelling treatment, the yellowing and blackening problems of cellulose in the phosphorylation reaction process are prevented, and the prepared reinforced PVA film achieves a better flame-retardant effect by adding a smaller amount of flame-retardant components on the premise that the mechanical property is improved and the transparency is not damaged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanocellulose reinforced PVA film technology and relates to a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film prepared based on secondary swelling. Background Art

[0002] In recent years, environmentally friendly polymer materials have attracted increasing attention from the research community due to their potential huge environmental benefits. Polyvinyl alcohol (PVA), as an environmentally friendly polymer, has good mechanical properties, excellent oil resistance, solvent resistance and non-toxicity, and can be produced industrially through non-petroleum routes. It has broad application prospects in packaging, soft electronics, electronic information and other fields. However, the limiting oxygen index of PVA is low, only 19-20%, it is flammable and has molten droplets, which can easily cause fire. For better application, many flame retardants that can be applied to PVA have been disclosed in the prior art, including halogen flame retardants, phosphorus flame retardants, and inorganic salt flame retardants. However, among these flame retardants, halogen flame retardants have been gradually banned due to their potential toxicity, and some classic halogen-free flame retardants such as ammonium polyphosphate and magnesium hydroxide are effective for PVA, but need to be added in large quantities (>25wt%), and due to the poor compatibility of the flame retardant with the PVA matrix, it is easy to agglomerate and precipitate, resulting in problems such as decreased mechanical properties of the product and low flame retardant durability. Developing flame retardants that are highly efficient, environmentally friendly, and have no side effects (especially on mechanical properties and transparency) has always been an ideal flame retardant solution.

[0003] In existing research, the excellent performance and environmental friendliness of bio-based flame retardants have been proven. Bio-based materials are a renewable resource that can be regenerated by photosynthesis. Cellulose is the most abundant biopolymer in nature, producing 1.1 billion tons of biomass per year. 10 ~1.10 11 Tons, present in various plants, bacteria, fungi. Cellulose contains a large number of hydroxyl groups and is easy to functionalize: there are three active hydroxyl functional groups at the C-2, C-3 and C-6 positions. The phosphorylation of cellulose is the most widely studied modification method. The phosphorylation reaction of cellulose can be achieved by hydroxyl functionalization with phosphoric acid or its salts, phosphoric acid, polyphosphorus compounds, phosphorus pentoxide or phosphorus pentasulfide, halogenated derivatives, phosphoric acid anhydride, or by grafting phosphorus-containing functional groups, which can improve the carbon-forming ability of cellulose and thus improve its flame retardant properties. For example: Khakalo et al. [1] Enzyme-assisted pulp disintegration was carried out under mild mechanical treatment and the fiberized material was treated with (NH 4 ) 2 HPO 4 The cellulose is effectively mixed and then phosphorylated to prepare the flame retardant fiber paper.

[0004] However, in the above methods and existing literature records, the prepared phosphorylated cellulose usually has serious yellowing and blackening phenomena, and the transparency of the product is also seriously affected. In order to solve the above problems, Xie et al. [2] A transparent phosphorylated cellulose film was prepared by a similar method. To ensure high transparency of the film (above 80%), the maximum phosphorus content of the sample could only reach 6.17%, making it difficult to use as a flame retardant.

[0005] Based on the above investigation, it was found that in the existing technology, the phosphorus content of phosphorylated cellulose and its easy degradation and discoloration have become a "seesaw" problem. If a colorless and transparent phosphorylated nanocellulose reinforced PVA film can be prepared without reducing the phosphorus content of phosphorylated cellulose, it will provide new ideas and solutions for flame retardant reinforced PVA film.

[0006] [1] Khakalo, A.; Jaiswal, AK; Kumar, V.; Gestranius, M.; Kangas, H.; Tammelin, T., Production of High-Solid-Content Fire-Retardant Phosphorylated Cellulose Microfibrils. ACS Sustainable Chemistry&Engineering 2021, 9(36), 12365-12375.

[0007] [2] Xie Hong. Preparation of phosphorylated nanocellulose and research on the properties of its nanopaper. Master, 2021. Summary of the invention

[0008] In order to solve the above problems in the prior art, the present invention provides a method for preparing a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film based on secondary swelling. The preparation method comprises the following steps: cellulose is initially swollen by a NaOH solution, and then a certain amount of urea and NH4OH are added. 4 H 2 PO 4 The nanocellulose is effectively mixed with cellulose, dried and then subjected to solid phase reaction, and the subsequent phosphorylation degree is increased during the secondary swelling (P element content 10-12.2%), and then homogenized to prepare phosphorylated nanocellulose with a high phosphorus content. As a filler, a flame-retardant, colorless and transparent reinforced PVA film can be prepared. Under the premise of improving mechanical properties and not destroying transparency, a smaller amount of flame-retardant components can be added to obtain a better flame-retardant effect.

[0009] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0010] The present invention provides a method for preparing a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film based on secondary swelling, which mainly comprises the following steps:

[0011] (1) immersing cellulose in a NaOH solution with a mass concentration of 2 to 15 wt% and stirring at a temperature of 30 to 80° C. for 10 to 60 minutes, and obtaining a primary swollen cellulose suspension after the time is up;

[0012] (2) the once swollen cellulose suspension obtained in step (1) is mixed with a phosphorylation modifier, and then the water is removed, and the mixture is reacted in a closed environment at a temperature of 140 to 160° C. for 0.5 to 2 hours. After the time is up, the mixture is cooled, the solid is separated, and the solid is washed to obtain phosphorylated cellulose;

[0013] Wherein, the phosphorylation modifier is NH 4 H 2 PO 4 and urea, the solid mass in the primary swollen cellulose suspension is equal to NH 4 H 2 PO 4 The mass ratio of urea is 1:(1.8~3.6):(4.8~9.8);

[0014] (3) preparing a phosphorylated cellulose suspension having a mass concentration of 3 to 5 wt % by preparing the phosphorylated cellulose obtained in step (2), and homogenizing the phosphorylated cellulose suspension to obtain a phosphorylated nanocellulose suspension;

[0015] (4) completely dissolving PVA in deionized water to prepare a PVA aqueous solution with a mass concentration of 5 to 15 wt%, mixing the phosphorylated nanocellulose suspension obtained in step (3) with the PVA aqueous solution as a film-making slurry, and performing film-making based on a conventional solution method to obtain a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film;

[0016] Wherein, the mass ratio of phosphorylated nanocellulose to PVA in the membrane-making slurry is 1:(5-20).

[0017] In this article, the cellulose in step (1) can be obtained by oneself or directly obtained from the market. Those skilled in the art can select a suitable source of cellulose according to the cost and production process requirements.

[0018] In one technical solution, the cellulose in step (1) is prepared by extracting biomass materials. Generally speaking, the biomass materials are crop materials collected during agricultural production, such as waste parts (such as straw, etc.) of crops such as wheat, corn, rice, barley, cotton, soybeans, and sugarcane.

[0019] It should be noted that the above-mentioned cellulose is prepared by extracting biomass materials. The specific process / method for preparing cellulose by extracting biomass materials has been documented in relevant technical literature. Those skilled in the art can directly refer to the content in the relevant technical literature or directly purchase cellulose prepared by extracting biomass materials. It should be emphasized that in the embodiments of this article, the cellulose used is prepared by extracting sugarcane bamboo pulp, but this is not the only designation or limitation on the source of cellulose.

[0020] The inventive point of the present invention is that, in the process of conducting experiments to analyze the "seesaw" problem between the phosphorus content of phosphorylated cellulose and its easy degradation and discoloration in the prior art, the inventor accidentally discovered that the NaOH solution commonly used in the process of removing lignin from the biomass material (the sugarcane bamboo pulp used in the experiment) can also swell the cellulose powder very well, and the cellulose swollen with the NaOH solution can significantly increase the phosphorus content of the phosphorylated cellulose in the subsequent phosphorylation reaction. At the same time, the prepared high-phosphorus content phosphorylated cellulose does not have the problem of yellowing and blackening, and is a pure white product. The reinforced PVA film prepared using it as a filler retains the colorless and highly transparent properties to the greatest extent.

[0021] Through further analysis, it is speculated that this is because the cellulose swollen with NaOH solution can effectively improve the reaction efficiency of the subsequent phosphorylation reaction, retain the cellulose crystal form and crystallinity to the greatest extent, and can prepare phosphorylated cellulose with a high phosphorus content at a lower temperature and in a shorter reaction time, thus avoiding the yellowing and blackening of cellulose due to degradation.

[0022] Based on the above invention, it is important to explain that the stirring at 30-80°C for 10-60 min in step (1) is performed; if the time exceeds 60 min, the NaOH solution will over-swell the cellulose, causing the cellulose crystals to swell and dissolve, reducing the crystallinity of the cellulose and affecting the subsequent preparation of phosphorylated cellulose. It is further preferred that the stirring is performed at 50-80°C for 20-45 min.

[0023] Based on the above invention, it should be emphasized that the reaction in step (2) is carried out in a closed environment at a temperature of 140-160° C. for 0.5-2 h. If the time exceeds 2 h or the temperature is higher than 160° C., excessive phosphorylation reaction will occur, and the cellulose will turn yellow and black due to degradation.

[0024] It should be noted that when the first swelled cellulose suspension obtained in step (1) is subjected to step (2), the first swelled cellulose suspension needs to be fully mixed with the phosphorylated modifier. Therefore, if the viscosity of the first swelled cellulose suspension is too high, it is not conducive to the dispersion effect of the phosphorylated modifier. Those skilled in the art should know that the viscosity of the first swelled cellulose suspension can be reduced by diluting the first swelled cellulose suspension. In order to better illustrate the present invention and provide a technical solution for reference, in step (2), the first swelled cellulose suspension obtained in step (1) is adjusted to a mass concentration of 3 to 10 wt%, and then fully mixed with the phosphorylated modifier. Under laboratory conditions, the full mixing in step (2) can be selected by mechanical stirring and / or ultrasonic treatment.

[0025] In addition, in step (2), the primary swelled cellulose suspension and the phosphorylated modifier are fully mixed and then the water is removed, and then reacted in a closed environment at a temperature of 140 to 160° C. for 0.5 to 2 hours. The essence of this is a solid phase reaction in a molten state of urea, and at the same time, the molten urea is used to form a secondary swelling of the cellulose. Usually, the removal of water is carried out under laboratory conditions by drying at a temperature of 60 to 110° C.

[0026] In this article, the homogenization treatment in step (3) is to further micronize and homogenize the phosphorylated cellulose using a homogenizer. In order to make the phosphorylated nanocellulose have higher transparency when reinforcing the PVA film, in one preferred technical solution, the phosphorylated nanocellulose obtained after the homogenization treatment in step (3) has a length average value of >1000nm and a diameter average value of ≤5nm.

[0027] It should be noted that those skilled in the art should be aware that during the homogenization process, the specific concentration of the phosphorylated cellulose suspension and the homogenization process parameters depend on the homogenizer used. Those skilled in the art can directly refer to the specific guidance on how to homogenize cellulose into nanocellulose in the prior art.

[0028] In this article, the Chinese name of PVA in step (4) is polyvinyl alcohol, and conventional industrial PVA raw materials in the field of this technology can be directly selected. Those skilled in the art can select appropriate PVA grades according to specific needs and process requirements, or refer to conventional PVA grades in the application field of the final product, especially the selection of PVA raw materials suitable as raw materials for film products in the prior art.

[0029] In one of the technical solutions, the PVA in step (4) preferably has a degree of polymerization of 1700 to 2600 and a degree of alcoholysis of 88 to 99%.

[0030] In one of the technical solutions, the PVA aqueous solution in step (4) may also be added with additives conventionally used in PVA processing and molding to achieve further functional expansion / process assistance of the product. For the specific selection of additives, those skilled in the art may refer to the prior art or existing literature, such as defoamers, antioxidants, heat stabilizers, plasticizers, antibacterial agents and other processing aids / functional additives. It should be noted that the PVA aqueous solution in step (1) may or may not include additives conventionally used in PVA processing and molding; in the following preferred technical solutions and specific implementations, in order to minimize the influencing factors in the comparative experiment, additives are not added to the PVA aqueous solution, but this does not mean that appropriate additives cannot be added to the PVA aqueous solution. However, it should be noted that the addition of the above-mentioned additives is based on not affecting the transparency of the prepared film. When selecting additives, additives that will not cause dyeing / color difference to the product should be selected, and the total amount of additives added should not exceed 10wt%.

[0031] Herein, the film is prepared based on a conventional solution method in step (4). Those skilled in the art may refer to conventional process modes / methods for film preparation based on a solution method in the prior art.

[0032] In order to better illustrate the present invention and provide a technical solution for reference, the film-making method based on the conventional solution method described in step (4) is to defoam the film-making slurry at a temperature of 25 to 80°C, pour it into a mold and dry it at a temperature of 25 to 80°C. After demolding, a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film is prepared.

[0033] The present invention has the following beneficial effects:

[0034] 1. The present invention provides a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film prepared based on secondary swelling, which retains the colorless and transparent properties of the PVA film to the greatest extent while having flame-retardant functionality with a high phosphorus content.

[0035] 2. The present invention provides a method for preparing a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film based on secondary swelling. The secondary swelling treatment can prevent the yellowing and blackening of cellulose during the phosphorylation reaction.

[0036] 3. The preparation method of the present invention is simple, and phosphorylated nanocellulose with a high phosphorus content is prepared, which can be used as a filler to prepare a flame-retardant, colorless and transparent reinforced PVA film. On the premise of improving mechanical properties and not destroying transparency, a smaller amount of flame-retardant ingredients can be added to obtain a better flame-retardant effect, and the film is suitable for use as a packaging material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1Comparative photographs of the cellulose suspension, the once swollen cellulose suspension, the phosphorylated cellulose suspension and the phosphorylated nanocellulose suspension in Example 1 of the present invention. From left to right, they are the cellulose suspension, the once swollen cellulose suspension, the phosphorylated cellulose suspension and the phosphorylated nanocellulose suspension, and all of them have been left to stand for 12 hours.

[0038] Figure 2 The XPS comparison spectra of the phosphorylated cellulose and the cellulose raw materials used in Example 1 and Comparative Example 2 of the present invention are shown. Among them, the phosphorylated cellulose prepared in Example 2 without swelling corresponds to the phosphorylated cellulose prepared in Example 2, and the phosphorylated cellulose prepared in Example 1 with swelling corresponds to the phosphorylated cellulose prepared.

[0039] Figure 3 Comparative photos of phosphorylated cellulose in Example 1 (left) of the present invention and Comparative Example 3 (right).

[0040] Figure 4 The UV spectra of the thin film samples prepared in Examples 1 to 4 and Comparative Example 1 of the present invention are compared and the transparency verification diagram is shown. Figure a is a UV spectra comparison diagram of the thin film samples prepared in Examples 1 to 4 and Comparative Example 1, 0wt%, 5wt%, 10wt%, 12.5wt%, 15wt% correspond to the thin film samples prepared in Comparative Example 1, Example 5, Example 4, Example 3, Example 2, and Example 1, respectively; Figure b1 is a transparency verification diagram of the thin film sample prepared in Comparative Example 1, and Figure b2 is a transparency verification diagram of the thin film sample prepared in Example 2.

[0041] Figure 5 This is a graph showing the XRD comparison results of the raw cellulose, the intermediate phosphorylated cellulose and the phosphorylated nanocellulose in Example 1 of the present invention.

[0042] Figure 6 It is a comparison diagram of the vertical combustion test results of the film samples prepared in Example 2 (lower) of the present invention and Comparative Example 1 (upper). DETAILED DESCRIPTION

[0043] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0044] The present invention provides a method for preparing a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film based on secondary swelling, which mainly comprises the following steps:

[0045] (1) immersing cellulose in a NaOH solution with a mass concentration of 2 to 15 wt% and stirring at a temperature of 30 to 80° C. for 10 to 60 minutes, and obtaining a primary swollen cellulose suspension after the time is up;

[0046] (2) the once swollen cellulose suspension obtained in step (1) is mixed with a phosphorylation modifier, and then the water is removed, and the mixture is reacted in a closed environment at a temperature of 140 to 160° C. for 0.5 to 2 hours. After the time is up, the mixture is cooled, the solid is separated, and the solid is washed to obtain phosphorylated cellulose;

[0047] Wherein, the phosphorylation modifier is NH 4 H 2 PO 4 and urea, the solid mass in the primary swollen cellulose suspension is equal to NH 4 H 2 PO 4 The mass ratio of urea is 1:(1.8~3.6):(4.8~9.8);

[0048] (3) preparing a phosphorylated cellulose suspension having a mass concentration of 3 to 5 wt % by preparing the phosphorylated cellulose obtained in step (2), and homogenizing the phosphorylated cellulose suspension to obtain a phosphorylated nanocellulose suspension;

[0049] (4) completely dissolving PVA in deionized water to prepare a PVA aqueous solution with a mass concentration of 5 to 15 wt%, mixing the phosphorylated nanocellulose suspension obtained in step (3) with the PVA aqueous solution as a film-making slurry, and performing film-making based on a conventional solution method to obtain a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film;

[0050] Wherein, the mass ratio of phosphorylated nanocellulose to PVA in the membrane-making slurry is 1:(5-20).

[0051] In this article, the cellulose in step (1) can be obtained by oneself or directly obtained from the market. Those skilled in the art can select a suitable source of cellulose according to the cost and production process requirements.

[0052] In one embodiment, the cellulose in step (1) is prepared by extracting biomass materials. Generally speaking, the biomass materials are crop materials collected during agricultural production, such as waste parts (such as straw, etc.) of crops such as wheat, corn, rice, barley, cotton, soybeans, and sugarcane.

[0053] It should be noted that the above-mentioned cellulose is prepared by extracting biomass materials. The specific process / method for preparing cellulose by extracting biomass materials has been documented in relevant technical literature. Those skilled in the art can directly refer to the content in the relevant technical literature or directly purchase cellulose prepared by extracting biomass materials. It should be emphasized that in the embodiments of this article, the cellulose used is prepared by extracting sugarcane bamboo pulp, but this is not the only designation or limitation on the source of cellulose.

[0054] The inventive point of the present invention is that, in the process of conducting experiments to analyze the "seesaw" problem between the phosphorus content of phosphorylated cellulose and its easy degradation and discoloration in the prior art, the inventor accidentally discovered that the NaOH solution commonly used in the process of removing lignin from the biomass material (the sugarcane bamboo pulp used in the experiment) can also swell the cellulose powder very well, and the cellulose swollen with the NaOH solution can significantly increase the phosphorus content of the phosphorylated cellulose in the subsequent phosphorylation reaction. At the same time, the prepared high-phosphorus content phosphorylated cellulose does not have the problem of yellowing and blackening, and is a pure white product. The reinforced PVA film prepared using it as a filler retains the colorless and highly transparent properties to the greatest extent.

[0055] Through further analysis, it is speculated that this is because the cellulose swollen with NaOH solution can effectively improve the reaction efficiency of the subsequent phosphorylation reaction, retain the cellulose crystal form and crystallinity to the greatest extent, and can prepare phosphorylated cellulose with a high phosphorus content at a lower temperature and in a shorter reaction time, thus avoiding the yellowing and blackening of cellulose due to degradation.

[0056] Based on the above invention, it is important to explain that the stirring at 30-80°C for 10-60 min in step (1) is performed; if the time exceeds 60 min, the NaOH solution will over-swell the cellulose, causing the cellulose crystals to swell and dissolve, reducing the crystallinity of the cellulose and affecting the subsequent preparation of phosphorylated cellulose. In one preferred embodiment, the stirring is further preferably performed at 50-80°C for 20-45 min.

[0057] Based on the above invention, it should be emphasized that the reaction in step (2) is carried out in a closed environment at a temperature of 140-160° C. for 0.5-2 h. If the time exceeds 2 h or the temperature is higher than 160° C., excessive phosphorylation reaction will occur, and the cellulose will turn yellow and black due to degradation.

[0058] It should be noted that when the first swelled cellulose suspension obtained in step (1) is subjected to step (2), the first swelled cellulose suspension needs to be fully mixed with the phosphorylated modifier. Therefore, if the viscosity of the first swelled cellulose suspension is too high, it is not conducive to the dispersion effect of the phosphorylated modifier. Those skilled in the art should know that the viscosity of the first swelled cellulose suspension can be reduced by diluting the first swelled cellulose suspension. In order to better illustrate the present invention and provide a technical solution for reference, in step (2), the first swelled cellulose suspension obtained in step (1) is adjusted to a mass concentration of 3 to 10 wt%, and then fully mixed with the phosphorylated modifier. Under laboratory conditions, the full mixing in step (2) can be selected by mechanical stirring and / or ultrasonic treatment.

[0059] In addition, in step (2), the primary swelled cellulose suspension and the phosphorylated modifier are fully mixed and then the water is removed, and then reacted in a closed environment at a temperature of 140 to 160° C. for 0.5 to 2 hours. The essence of this is a solid phase reaction in a molten state of urea, and at the same time, the molten urea is used to form a secondary swelling of the cellulose. Usually, the removal of water is carried out under laboratory conditions by drying at a temperature of 60 to 110° C.

[0060] In one embodiment, the solid mass of the first swollen cellulose suspension in step (2) is NH 4 H 2 PO 4The mass ratio of the solid mass to the urea in the first swollen cellulose suspension in step (2) is 1:(4.8-9.8), for example 1:4.8, 1:4.9, 1:5.0, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5, 1:5.6, 1:5.7, 1:5.8, 1:5.9, 1:6.0, 1:6.1, 1:6.2, 1:6.3, 1:6.4, 1:6.5, 1:6.6, 1:6.7, 1:6.8, 1:6.9, 1:7.0, 1:7.1, 1:7.2, 1:7.3, 1:7.4, 1:7.5, 1:7.6, 1:7.7, 1:7.8, 1:7.9, 1:8.0, 1:8.1, 1:8.2, 1:8.3, 1:8.4, 1:8.5, 1:8.6, 1:8.7, 1:8.8 5.8, 1:5.9, 1:6.0, 1:6.1, 1:6.2, 1:6.3, 1:6.4, 1:6.5, 1:6.6, 1:6.7, 1:6.8, 1:6.9, 1:7, 1:7.1, 1:7.2, 1:7.3, 1:7.4, 1:7.5, 1:7.6, 1:7.7, 1:7.8, 1:7.9 , 1:8.0, 1:8.1, 1:8.2, 1:8.3, 1:8.4, 1:8.5, 1:8.6, 1:8.7, 1:8.8, 1:8.9, 1:9.0, 1:9.1, 1:9.2, 1:9.3, 1:9.4, 1:9.5, 1:9.6, 1:9.7, 1:9.8 or any range or point value therebetween.

[0061] In this article, the homogenization treatment in step (3) is to further micronize and homogenize the phosphorylated cellulose using a homogenizer. In order to make the phosphorylated nanocellulose obtained have higher transparency when reinforcing the PVA film, in one preferred embodiment, the phosphorylated nanocellulose obtained after the homogenization treatment in step (3) has a length average value of >1000nm and a diameter average value of ≤5nm.

[0062] It should be noted that those skilled in the art should be aware that during the homogenization process, the specific concentration of the phosphorylated cellulose suspension and the homogenization process parameters depend on the homogenizer used. Those skilled in the art can directly refer to the specific guidance on how to homogenize cellulose into nanocellulose in the prior art.

[0063] In this article, the Chinese name of PVA in step (4) is polyvinyl alcohol, and conventional industrial PVA raw materials in the field of this technology can be directly selected. Those skilled in the art can select appropriate PVA grades according to specific needs and process requirements, or refer to conventional PVA grades in the application field of the final product, especially the selection of PVA raw materials suitable as raw materials for film products in the prior art.

[0064] In one embodiment, the PVA in step (4) preferably has a degree of polymerization of 1700 to 2600 and a degree of alcoholysis of 88 to 99%.

[0065] In one embodiment, the PVA aqueous solution in step (4) may also be added with additives conventionally used in PVA processing and molding to achieve further functional expansion / process assistance of the product. The specific selection of additives can be referenced by those skilled in the art based on the prior art or existing literature, such as defoamers, antioxidants, heat stabilizers, plasticizers, antibacterial agents and other processing aids / functional additives. It should be noted that the PVA aqueous solution in step (1) may include or not include additives conventionally used in PVA processing and molding; in the following preferred technical scheme and specific implementation, in order to minimize the influencing factors in the comparative experiment, additives are not added to the PVA aqueous solution, but this does not mean that appropriate additives cannot be added to the PVA aqueous solution. However, it should be noted that the addition of the above-mentioned additives is based on not affecting the transparency of the prepared film. When selecting additives, additives that will not cause dyeing / color difference to the product should be selected, and the total amount of additives added should not exceed 10wt%.

[0066] Herein, the film is prepared based on a conventional solution method in step (4). Those skilled in the art may refer to conventional process modes / methods for film preparation based on a solution method in the prior art.

[0067] In order to better illustrate the present invention and provide an implementation method for reference, the film-making method based on the conventional solution method described in step (4) is to defoam the film-making slurry at a temperature of 25 to 80°C, pour it into a mold and dry it at a temperature of 25 to 80°C. After demolding, a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film is prepared.

[0068] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0069] Example

[0070] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0071] 1. Raw materials

[0072] Polyvinyl alcohol (PVA) (degree of polymerization 1700, degree of alcoholysis 99%), supplied by Sichuan Vinylon Co., Ltd.;

[0073] The cellulose was obtained by itself from commercially available sugarcane pulp as raw material;

[0074] NH 4 H 2 PO 4 , urea, and NaOH were provided by Aladdin;

[0075] Distilled water was used throughout the experiments.

[0076] 2. Test Method

[0077] 1) Tensile performance test

[0078] The film samples were cut into dumbbell-shaped specimens and subjected to tensile property tests at a speed of 20 mm / min using an electronic universal material testing machine.

[0079] 2) Scanning electron microscope test (SEM)

[0080] The microstructure of cellulose, film samples and carbon residues was analyzed by SEM (Apreo S HiVo) at 10 kV. Before testing, a layer of platinum was coated on the samples. Before cross-sectional analysis, the samples were immersed in liquid nitrogen for brittle fracture. The surface element content of the film cross section and carbon residue was determined by EDS (Octane Elect Super).

[0081] 3) X-ray Photoelectron Spectroscopy (XPS)

[0082] The composition of the chemical bonds on the surfaces of phosphorylated cellulose and residual carbon samples was analyzed. The original spectra were corrected and calibrated with the carbon-carbon single bond peak at 284.6 eV, and quantitative analysis was performed using CasaXPS software.

[0083] 4) Homogenization

[0084] Homogenization was performed using a microfluidizer (NOOZLE Nano) at a pressure of 6000 psi.

[0085] 5) Limiting Oxygen Index (LOI)

[0086] According to the standard of ASTM D 2863-77, the LOI value was measured using the LOI tester (Nanjing Jiangning Analytical Instrument Co., Ltd.), with a size of 100×50×0.1mm 3 .

[0087] 6) Vertical burning test

[0088] The flame retardant grade is tested by UL-94 (Dongguan Jinte Instrument Co., Ltd.), according to GB / T 2408-2008 standard, and the size is 125.0×50.0×0.1mm 3 .

[0089] 7) Cone Combustion Calorimetry

[0090] According to ISO 5660 standard, the flame retardant properties of the film samples were characterized using a British FTT-0476 cone calorimeter (size 100×100×4mm3).

[0091] 8) Transmission Electron Microscopy (TEM)

[0092] Transmission electron microscopy (TEM) images of phosphorylated nanocellulose were obtained using a Tecnai G2 F20 S-TWIN (FEI, USA) with an accelerating voltage of 60 kV. The samples were prepared by dropping sample aqueous solutions on copper grids and stained with phosphotungstic acid negative staining solution (2%) for 3 min before testing.

[0093] 9) Thermogravimetric analysis-infrared analysis

[0094] The gaseous volatiles at 50-900 °C were analyzed by TG-FTIR (TGA8000-FTIR spectrometer, Perkin Elmer) at a heating rate of 30 °C / min, with the atmosphere being air.

[0095] 10) Ultraviolet Visible Spectrophotometer (UV)

[0096] The UV spectrum of the film sample was obtained using a Shimadzu UV-1750 UV-visible spectrophotometer with a slit width of 2 mm.

[0097] 11) Thermogravimetric analysis (TGA)

[0098] The thermal stability of the samples was measured using TAQ50 (TAInstrument Co. Ltd, New Castle, DE, USA) in a nitrogen atmosphere.

[0099] 3. Preparation method

[0100] (1) immersing cellulose in a NaOH solution with a mass concentration of 2 wt% and stirring at 60°C for 30 min. After the time is up, a primary swollen cellulose suspension with a cellulose mass concentration of 10 wt% is obtained;

[0101] (2) the once swollen cellulose suspension obtained in step (1) and the phosphorylation modifier are fully mixed, dried at 105° C. to remove moisture, reacted in a closed environment at 145° C. for 1.5 h, cooled, and separated by vacuum filtration after the solid is washed to obtain phosphorylated cellulose;

[0102] Wherein, the phosphorylation modifier is NH 4 H 2 PO 4 and urea, the solid mass in the primary swollen cellulose suspension is equal to NH 4 H 2 PO 4 The mass ratio of urea is 1:1.8:7.35;

[0103] (3) preparing a 4 wt % phosphorylated cellulose suspension by mixing the phosphorylated cellulose obtained in step (2) with water, and homogenizing the mixture to obtain a phosphorylated nanocellulose suspension;

[0104] (4) completely dissolving PVA in deionized water to prepare a PVA aqueous solution with a mass concentration of 10 wt%, mixing the phosphorylated nanocellulose suspension obtained in step (3) with the PVA aqueous solution as a film-making slurry, and performing film-making based on a conventional solution method to obtain a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film;

[0105] Wherein, the mass ratio of phosphorylated nanocellulose to PVA in the film-making slurry is 1:(5-20);

[0106] The conventional solution method is used for film making, which comprises the following steps: subjecting the film making slurry to vacuum defoaming treatment at 80°C, pouring it into a mold and drying it at 60°C, and after demoulding, a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film is prepared as a film sample. The thickness of the prepared film sample is controlled within the range of 80 to 100 μm by controlling the mass of the solid matter therein.

[0107] Example 1

[0108] Example 1 is a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film prepared as a film sample according to the above "3. Preparation method", wherein the mass ratio of phosphorylated nanocellulose to PVA in the film-making slurry in step (4) is 1:5.67, that is, the mass concentration of phosphorylated nanocellulose in the solid matter of the film-making slurry is 15wt%.

[0109] Example 2

[0110] Example 2 is a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film prepared as a film sample according to the above "3. Preparation method", wherein the mass ratio of phosphorylated nanocellulose to PVA in the film-making slurry in step (4) is 1:7, that is, the mass concentration of phosphorylated nanocellulose in the solid matter of the film-making slurry is 12.5wt%.

[0111] Example 3

[0112] Example 3 is a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film prepared as a film sample according to the above "3. Preparation method", wherein the mass ratio of phosphorylated nanocellulose to PVA in the film-making slurry in step (4) is 1:9, that is, the mass concentration of phosphorylated nanocellulose in the solid matter of the film-making slurry is 10wt%.

[0113] Example 4

[0114] Example 4 is a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film prepared as a film sample according to the above "3. Preparation method", wherein the mass ratio of phosphorylated nanocellulose to PVA in the film-making slurry in step (4) is 1:19, that is, the mass concentration of phosphorylated nanocellulose in the solid matter of the film-making slurry is 5wt%.

[0115] Verification Example 1

[0116] In order to verify the swelling effect of the secondary swelling in the present invention, cellulose and water were mixed to prepare a cellulose suspension with a cellulose mass concentration of 1 wt % as verification sample 1;

[0117] The cellulose was immersed in a NaOH solution with a mass concentration of 2 wt% and stirred at 60°C for 30 minutes. After the time was up, a primary swelled cellulose suspension with a cellulose mass concentration of 1 wt% was obtained as verification sample 2;

[0118] A primary swollen cellulose suspension having a cellulose mass concentration of 1 wt% is prepared according to step (2) of the above “3. Preparation method” to obtain phosphorylated cellulose, and mixed with water to prepare a phosphorylated cellulose suspension having a phosphorylated cellulose mass concentration of 1 wt% as verification sample three;

[0119] The phosphorylated nanocellulose suspension obtained by homogenizing a 1 wt % phosphorylated cellulose suspension was used as verification sample four.

[0120] Comparative Example 1

[0121] In Comparative Example 1, without adding phosphorylated nanocellulose, PVA was directly film-formed based on a conventional solution method to prepare a PVA film with the same thickness of 80 to 100 μm as a comparative sample.

[0122] Comparative Example 2

[0123] In Comparative Example 2, without undergoing a single swelling treatment with a NaOH solution, cellulose and water were mixed to prepare a cellulose suspension having a cellulose mass concentration of 10 wt%, the cellulose suspension and the phosphorylation modifier were fully mixed and then dried at 105° C. to remove moisture, and the mixture was reacted at 145° C. in a closed environment for 1.5 h. After the time was up, the mixture was cooled and vacuum filtered to separate the solid, and washed to obtain phosphorylated cellulose;

[0124] Wherein, the phosphorylation modifier is NH 4 H 2 PO 4 and urea, the solid mass in the cellulose suspension is equal to NH 4 H 2 PO 4 The mass ratio of urea is 1:1.8:7.35.

[0125] Comparative Example 3

[0126] In Comparative Example 3, the cellulose was not swollen once with the NaOH solution. In order to prepare phosphorylated cellulose having the same phosphorus content as in Examples 1 to 4, the following steps were specifically performed:

[0127] The cellulose and water are mixed to prepare a cellulose suspension with a cellulose mass concentration of 10 wt %, the cellulose suspension and the phosphorylation modifier are fully mixed, and then dried at 105° C. to remove moisture, and reacted at 170° C. in a closed environment for 1.5 hours. After the time is up, the solid is separated by vacuum filtration after cooling and washed to obtain phosphorylated cellulose;

[0128] Wherein, the phosphorylation modifier is NH 4 H 2 PO 4 and urea, the solid mass in the cellulose suspension is equal to NH 4 H 2 PO 4 The mass ratio of urea is 1:1.8:7.35.

[0129] The phosphorus content of the prepared phosphorylated cellulose is about 10%.

[0130] Comparative Example 4

[0131] In Comparative Example 4, the cellulose was not swollen once with the NaOH solution. In order to prepare phosphorylated cellulose having the same phosphorus content as in Examples 1 to 4, the following steps were specifically performed:

[0132] The cellulose and water are mixed to prepare a cellulose suspension with a cellulose mass concentration of 10 wt%, the cellulose suspension and the phosphorylation modifier are fully mixed, and then dried at 105° C. to remove moisture, and reacted at 145° C. in a closed environment for 3 hours. After the time is up, the solid is separated by vacuum filtration after cooling and washed to obtain phosphorylated cellulose;

[0133] Wherein, the phosphorylation modifier is NH 4 H 2 PO 4 and urea, the solid mass in the cellulose suspension is equal to NH 4 H 2 PO 4 The mass ratio of urea is 1:1.8:7.35.

[0134] The phosphorus content of the prepared phosphorylated cellulose is about 10%.

[0135] 4. Test Results

[0136] like Figure 1 As shown, in Verification Example 1, the pretreatment with NaOH solution caused the cellulose to swell, which can further promote the phosphorylation modification of cellulose.

[0137] like Figure 2 As shown, the cellulose with and without NaOH solution swelling was subjected to the same phosphorylation reaction by XPS. Through quantitative analysis, the phosphorus content of the phosphorylated cellulose without NaOH solution swelling was only about 4-6%, while after swelling once, the phosphorus content increased greatly and reached about 10-12.2%.

[0138] like Figure 3 As shown, in Comparative Examples 3 and 4, in order to achieve phosphorylated cellulose with the same phosphorus content as in Examples 1 to 4, the reaction temperature can only be increased or the reaction time can be extended, but excessive phosphorylation reaction often causes cellulose to decompose, causing the cellulose to turn yellow and black. However, after a swelling treatment with NaOH solution, the prepared phosphorylated cellulose still retains the original color of cellulose.

[0139] Adding flame retardants to traditional flame retardant methods will cause the transparency of film products to decrease significantly. Figure 4As shown, it can be seen from the UV spectrum and the actual picture that the flame-retardant PVA film samples prepared in Examples 1 to 4 of the present invention are colorless and have good transparency. In the wavelength range of 500 to 800 nm, the transparency of the film sample with a phosphorylated nanocellulose mass concentration of 12.5wt% is 82.5%, which is almost equivalent to the pure PVA film (86.0%). Among them, the film sample with a phosphorylated nanocellulose mass concentration of 12.5wt% can pass the V-0 grade of the UL-94 test, and the LOI value reaches 28%.

[0140] like Figure 5 As shown, it can be seen that the cellulose, phosphorylated cellulose and phosphorylated nanocellulose after homogenization after single swelling treatment with NaON all retain the characteristic peaks of the original cellulose, and their crystal structures remain consistent. However, due to mechanical and physical effects, the diffraction peak of phosphorylated nanocellulose at 34.6° disappears, indicating that the mechanical effect destroys its crystallinity.

[0141] like Figure 6 As shown, the flame retardancy of the film samples of Example 2 and Comparative Example 1 was compared and studied by UL-94 test. Since PVA is flammable and the film is thin, it has no test grade during the UL-94 test. After adding phosphorylated nanocellulose, the flame retardancy of the reinforced PVA film sample is improved, and it can reach the VTM-0 grade of self-extinguishing from fire and finally pass the UL-94 test.

[0142] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film based on secondary swelling, characterized in that The main steps include: (1) immersing cellulose in a NaOH solution with a mass concentration of 2 to 15 wt% and stirring at a temperature of 30 to 80° C. for 10 to 60 minutes, and obtaining a primary swollen cellulose suspension after the time is up; (2) the once swollen cellulose suspension obtained in step (1) is mixed with a phosphorylation modifier, and then the water is removed, and the mixture is reacted in a closed environment at a temperature of 140 to 160° C. for 0.5 to 2 hours. After the time is up, the mixture is cooled, the solid is separated, and the solid is washed to obtain phosphorylated cellulose; The phosphorylation modifier is prepared by mixing NH4H2PO4 and urea, and the ratio of the solid mass to the mass of NH4H2PO4 and urea in the primary swelled cellulose suspension is 1:(1.8-3.6):(4.8-9.8); (3) preparing a phosphorylated cellulose suspension having a mass concentration of 3 to 5 wt % by preparing the phosphorylated cellulose obtained in step (2), and homogenizing the phosphorylated cellulose suspension to obtain a phosphorylated nanocellulose suspension; (4) completely dissolving PVA in deionized water to prepare a PVA aqueous solution with a mass concentration of 5 to 15 wt%, mixing the phosphorylated nanocellulose suspension obtained in step (3) with the PVA aqueous solution as a film-making slurry, and performing film-making based on a conventional solution method to obtain a colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film; Wherein, the mass ratio of phosphorylated nanocellulose to PVA in the membrane-making slurry is 1:(5-20).

2. The method according to claim 1, characterized in that: The cellulose in step (1) is prepared by extracting biomass materials.

3. The method according to claim 1, characterized in that: In step (1), the cellulose is immersed in a NaOH solution with a mass concentration of 2 to 15 wt% and stirred at a temperature of 50 to 80° C. for 20 to 45 minutes.

4. The method according to claim 1, characterized in that: The phosphorylated nanocellulose obtained after homogenization in step (3) has an average length of >1000nm and an average diameter of ≤5nm.

5. The method according to claim 1, characterized in that: The PVA in step (4) is a PVA with a polymerization degree of 1700-2600 and an alcoholysis degree of 88-99%.

6. The method according to claim 1, characterized in that: The PVA aqueous solution in step (4) also includes auxiliary agents conventionally used in PVA processing and molding, and the total amount of the auxiliary agents added is not higher than 10wt%.

7. A colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film prepared by the method for preparing a colorless, highly transparent, flame-retardant, phosphorylated nanocellulose reinforced PVA film based on secondary swelling as described in claim 1.

8. Use of the colorless, highly transparent, flame-retardant phosphorylated nanocellulose reinforced PVA film as claimed in claim 7 as a packaging material.

Citation Information

Patent Citations

  • Preparation method of regenerative and antibacterial cellulose-polyvinyl alcohol composite membrane

    CN104629067A

  • Phosphorus-containing essence inflaming-retarding cellulose-based thermal insulation material and preparation method thereof

    CN109942882A

  • Surface coated cellulose film

    CN114599714A

  • PVA fiber and nano ZnO / epoxy resin composite material and preparation method thereof

    CN117103732A

  • A method for preparing a cellulose based material

    WO2015142159A1

Cited By

  • Preparation method of core-shell structure flame retardant and application of prepared flame retardant

    CN121779793A